Reexamining the relationships among urbanization, industrial structure, and environmental pollution in China: New evidence using the dynamic threshold panel model - Hao Yu; Shaoqing Zheng; Mingyuan Zhao; Haitao Wu; Yunxia Guo; Yunwei Li (Energy Reports, 2020)
Since China's reform and opening up, the urban economy has substantially developed, and the nation's urbanization process has advanced to gradually enter a "new normal" phase. In this process, China's population and industries continue to inundate its cities, and environmental pollution has become a critical problem. This study uses panel data spanning 1998 to 2015 from 29 Chinese provinces and a comprehensive framework of well-designed generalized method of moments (GMM) models to accurately examine the relationships between urbanization and per capita sulfur dioxide (PSO2), per capita industrial soot (PSOOT), and per capita industrial waste gas (PIWG). A newly developed dynamic threshold panel model that incorporates GMM characteristics is utilized to explore how urbanization affects environmental pollution under different industrial structures. This study finds evidence of a comprehensive relationship among urbanization development, the industrial structure, and environmental pollution. Urbanization has contributed to increased environmental pollution. A nonlinear relationship exists between urbanization and environmental pollution in China. Further, urbanization increasingly promotes environmental pollution with an increase in the proportion of secondary industries; however, such promotion decreases with an increase in the proportion of tertiary industries.
Keywords: 330; Urbanization; Industrial structure; Environmental pollution; Dynamic threshold panel model; China